What drives input subsidy policy reform? The case of Zambia, 2002–2016 - Resnick, Danielle; Mason, Nicole, M. (International Food Policy Research Institute, 2016)
When and why do suboptimal agricultural policies persist despite technical evidence highlighting alternatives? And what explains episodes of reform after prolonged periods of policy inertia? This paper addresses these questions by applying the Kaleidoscope Model for agricultural and food security policy change to the specific case of agricultural input policy in Zambia. Since 2002, the Farmer Input Support Program (formerly the Fertilizer Support Program) has been a cornerstone of Zambia’s agricultural policy. Over the years, however, many researchers have highlighted weaknesses in the program and proposed other options. Based on semistructured interviews with key stakeholders and intensive process tracing using media, donor, parliamentary, and research reports, this paper examines how the program initially began in 2002 and during subsequent periods of reform in 2009 and 2015. Based on the findings here, periods of reform for input support programs are most likely when there is a confluence of multiple factors. These include the emergence of a window of opportunity in the form of either a focusing event (for example, a food crisis) or an institutional shift (for example, a new president or new ruling party) that coincides with broad stakeholder support for empirically grounded alternatives, available material resources, and sustained commitment from politically important policy makers.